Partial Replacement of Fish Meal with Protein Hydrolysates in the Diet of Penaeus vannamei (Boone, 1934) during the Nursery Phase - Negrini, Celma; Nascimento Ferreira, Caio Henrique do [UNESP]; Kracizy, Rafael Ortiz; Ferreira, Rosane Lopes; Costa, Luana; Mauerwerk, Marlise Teresinha; Retcheski, Milena Cia; Cazarolli, Luisa Helena; Boscolo, Wilson Rogério; Cupertino Ballester, Eduardo Luis (MDPI, 2024)
The objective was to evaluate the effects of partial replacement of fish meal with protein hydrolysates and a commercial product in the diets of Penaeus vannamei post-larvae on zootechnical performance, proximate chemical composition, digestive enzyme activity, and total hemocyte count. The experiment was conducted in a clear water recirculation system comprising 24 experimental units, each with 30 shrimp with an average weight of 0.2 g. The treatments were control, chicken protein hydrolysate (CPH), enzymatic hydrolysate of chicken feathers, Aquabite®, CPH + maltodextrin, and CPH + yeast, with four replicates each. The inclusion level of the different protein sources evaluated was 6%. At the end of the experiment, all shrimp were counted, weighed, and measured to determine the zootechnical performance. The body and feed chemical compositions, as well as the enzymatic activities of the hepatopancreas and the total hemocyte count in the hemolymph, were analyzed. The data obtained were subjected to ANOVA and Tukey’s test. There was no statistical difference between the treatments in any of the analyzed parameters. The results showed that all the evaluated protein hydrolysates can be used as partial substitutes for fish meal in P. vannamei diets during the nursery phase, maintaining equivalent and adequate digestive enzyme activities, health, growth, and body composition of the shrimp, in addition to being ecologically sustainable ingredients.
Keywords: aquaculture; hydrolysis; nutrition; Pacific white shrimp; peptides; protein